Clustering technique to improve ability of generating ideas in recount text writing - Hilda Mutia Sari; Yohanes Gatot Sutapa; Clarry Sada (UPT Bahasa Universitas Tanjungpura, 2021)
One of learners’ difficulties in the English language subject is writing. It also happened at MTs Darussalam Sengkubang, Kalimantan Barat. This classroom action research was conducted in the MTs to solve the learners’ difficulty in writing recount texts. The classroom action research that was used in this study consisted of planning, acting, observing, and reflecting in cyclical process. In this research, the data were collected using field note, observation checklist, interview guideline, documentation, and individual test. The finding was that there was improvement on learners’ behavior in the process of teaching and learning through the implementation of clustering technique. The researcher concluded that clustering technique was improving the learners’ ability in generating ideas in recount text writing. Therefore,clustering technique could help the learners in learning process because this technique encouraged learners to learn actively.